Determinants of Compliance to Good Agricultural Practices among Cocoa Farmers in Ondo State, Nigeria - Nathaniel Siji Olutegbe; Abdullahi Oluwadamilola Sanni (Caraka Tani: Journal of Sustainable Agriculture, 2021)
Cocoa is one of Nigeria’s most important agricultural commodities due to its status as a source of foreign exchange earnings. However, low quality and hence low patronage of cocoa beans of Nigeria origin has reduced this fortune in recent years due mainly to non-adherence to Good Agricultural Practices (GAP) among farmers. The study therefore identified the determinants of compliance to GAP among cocoa farmers in Ondo State, Nigeria. A three-stage sampling procedure was used to select 20% (150) of cocoa farmers across randomly sampled cocoa-producing communities in Ondo State. Information was sourced using a well-structured, validated questionnaire. Data were analyzed using frequency counts, mean and Ordinary Least Square (OLS). Majority of farmers had good knowledge of GAP. However, farmers were mostly faced with constraints such as high cost of agrochemicals and labor scarcity. Farmers rated economic benefits of GAP as high; while health and environmental benefits were rated low; with high acceptability of cocoa; utilization of soil organic matter and prevention of respiratory malfunctioning identified as top economic, environmental and health benefits, respectively. Although the general compliance was high across different GAP, practices to which farmers were least compliant were however of relatively high economic, health and environmental implications. Knowledge, perceived health and perceived economic benefits of GAP were important determinants of compliance. The extension unit of the Ondo State Ministry of Agriculture should prioritize sensitization and education of farmers on the economic, health and environmental benefits of GAP of cocoa in order to ensure profitability and sustainability of production.